Evaluation on the possibility of sound conduction independent of tympanic air cavity for severe tympanic adhesion patients by finite element analysis - Qin, Xiao; Yin, Yue; Sun, Huiying; Feng, Guodong; Gao, Zhiqiang (Frontiers in Bioengineering and Biotechnology, 2023)
Background: For patients with severe tympanic adhesion, reconstructing the tympanic air cavity is often challenging, resulting in poor hearing reconstruction outcomes. Therefore, establishing a sound conduction pathway independent of the tympanic air cavity may be a viable method for reconstructing hearing in these patients.The objective of this study was to evaluate the feasibility of sound conduction independent of the tympanic air cavity (i.e. replacing the original cavity with a tympanic vibrating material) using finite element analysis.We established a sound-structure coupling finite element model of the tympanum vibration conduction system, which included the tympanic membrane (TM), ossicular prosthesis, and tympanic vibrating material. This model was used to simulate middle ear vibrations under sound pressure, and we extracted the frequency response curve of the ossicular prosthesis' vibration displacement amplitude to evaluate the sound conduction effect of the middle ear. Next, we adjusted the structural and mechanical parameters of the tympanic vibrating material to analyze its impact on the sound conduction effect of the middle ear. Finally, we compared the frequency response curve of the stapes footplate in normal subjects to evaluate the feasibility of sound conduction independent of the tympanic air cavity.The Shell tympanic vibrating material had a better vibration conduction effect compared to solid or porous tympanic vibrating material. The vibration amplitude decreases with the increasing elastic modulus of the tympanic vibrating material.Implantation of 40kPa-shell tympanic vibrating material had the lowest hearing loss less than 5dB, and the hearing loss with 1MPa-porous tympanic vibrating material was largest and less than 25dB.Our study suggests that replacing the tympanic air cavity with a tympanic vibrating material is feasible. The establishment of a sound conduction pathway independent of the tympanic air cavity could potentially provide a method for hearing reconstruction in patients with severe tympanic adhesion.